Políticas gubernamentales y políticas públicas. El ciclo de las políticas de desarrollo del Gobierno de Michoacán, 2003-2010 - Arias Torres, Daniela (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The present research was the goal to determine to what extent the way it made the definition of the problem, the design, the implementation and the monitoring / evaluation (stages of publics policy) affected the natural sequence of the cycle development policies of the government of Michoacan during the period 2003- 2010. The hypothesis was proposed that the way to operate these stages negatively affected the sequence of the policy cycle in question. With the construction and operation of indicators, some indexes were calculated for each stage. The indexes allowed putting the stages in a certain position. The four stages are in a position acceptable regularly, present a series of technical and political problems. In applying the coefficient of determination (r 2S ) determined the sequence of cycle of development policy is affected by 85% by the definition of the problem, the design, implementation and monitoring/evaluation. Each stage is linked to the other, one influences the other and vice versa. As the definition of the problem has an index acceptable regularly, the others stages have similar indexes. The interrelation between them is constant, the feedback back to any of the other stages. This analysis allows validating the general hypothesis raised. The research precise the development policies of the government of Michoacan are considerably far from the "public". These try about policies governmental. There aren’t public policies. In the public policy the decisions are shared equally balance with non-governmental actors and the government. The development policies in Michoacán are formulated asymmetrical: the decisions are inclined toward the part governmental. It seems that the criterion that permit to validate the "acceptable level" of public policy lies in the articulation of technical knowledge with social demands, and criteria for determining these depends on a democratic political process.

La presente investigación tuvo como objetivo determinar en qué medida la forma en que se realizó la definición del problema, el diseño, la implementación y el seguimiento/evaluación (etapas de las políticas públicas) afectó la secuencia natural del ciclo de las políticas de desarrollo del gobierno de Michoacán durante el periodo 2003-2010. En la hipótesis se planteó que la manera de operar estas etapas afectó negativamente la secuencia del ciclo de las políticas en cuestión. Con la construcción y operación de indicadores, se calcularon índices para cada etapa. Los índices permitieron colocar a las etapas en una determinada posición. Las cuatro etapas se encuentran en una posición regularmente aceptable, presentan una serie de problemas técnicos y políticos. Al aplicar el coeficiente de determinación (r 2S ), se determinó que la secuencia del ciclo de las políticas de desarrollo es afectada en un 85% por la definición del problema, por el diseño, por la implementación y por el seguimiento/evaluación. Cada una de las etapas está relacionada con las otras, una influye en las demás y viceversa. Como la definición del problema tiene un índice regularmente aceptable, las otras etapas tienen índices parecidos. La interrelación entre ellas es permanente, la retroalimentación regresa a cualquiera de las otras etapas. Este análisis permite validar la hipótesis general planteada. En la investigación, se precisa que las políticas de desarrollo del gobierno de Michoacán se alejan considerablemente de lo “público”. Se trata de políticas gubernamentales. No son políticas públicas. En las políticas públicas las decisiones se comparten de manera equilibrada entre los actores no gubernamentales y el gobierno. Las políticas de desarrollo de Michoacán se formulan de forma asimétrica: las decisiones se inclinan hacia la parte gubernamental.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias del Desarrollo Regional
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/366; info:eu-repo/classification/cti/5; ININEE-D-2012-0002; Participación ciudadana; Plan estatal de desarrollo; Ciclo de política pública; Comités de desarrollo comunitario; CONEVAL